Clinical manifestations and long-term symptoms associated with SARS-CoV-2 omicron infection in children aged 0–17 years in Beijing: a single-center study - Li, Jing; Li, Jingjing; Cao, Ling; Wang, Lin; Chen, Xiaobo; Niu, Wenquan; Dang, Li; Dai, Shuzhi; Wang, Ying; Ge, Menglei; Liu, Weijie; Song, Qinwei; et al. (Frontiers in Pediatrics, 2024)
The study aims to analyze the clinical characteristics of acute phase of SARS-CoV-2 infection in children aged 0-17 years with the Omicron variant, and the persistent symptoms from 4 to 12 weeks after acute COVID. Explore the association between the vaccination status and SARS-CoV-2 neutralizing antibody levels post infection among preschool-aged children. Methods: The study enrolled children who were referred to the Children's Hospital, Capital Institute of Pediatrics. Participants were classified as infant and toddlers, preschool, school-age, and adolescent groups. Children or their legal guardians completed survey questionnaires to provide information of previous SARS-CoV-2 infection history, as well as clinical presentation during the acute phase and long-term symptoms from 4 to 12 weeks following infection. Serum samples were collected from children for serological testing of neutralizing antibodies. The study recruited a total of 2,001 children aged 0-17 years confirmed SARS-CoV-2 infection. Fever was the predominant clinical manifestation in 1,902 (95.5%) children. Cough was the common symptom in 777 (38.8%) children, followed by sore throat (22.1%), nasal congestion (17.8%), and running nose (17.2%). Fatigue (21.6%), headache (19.8%) and muscle-joint pain (13.5%) were frequently reported systemic symptoms in children. The proportion of children with symptoms of SARS-CoV-2 infection varied across age groups. 1,100 (55.0%) children experienced persistent symptoms from 4 to 12 weeks post the acute phase of infection. Trouble concentrating (22.1%), cough (22.1%), and fatigue (12.1%) were frequently reported across age groups in the extended period. Among 472 children aged 3-5 years, 208 children had received two doses of SARS-CoV-2 vaccine at least 6 months prior to infection, and no association was found between the incidence of long-term COVID and pre-infection vaccination statuses among the 3-5 years age groups. The incidence of persistent symptoms of SARS-CoV-2 did not exhibit a significant correlation with vaccination status, which was attributed to the waning efficacy of the vaccine-induced humoral immune response after 6 months.